Does the German minimum wage benefit low income households? - Teresa Backhaus; Kai-Uwe Müller (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Previous literature on the distributional impact of the minimum wage in Germany has either focused on earnings and hourly wages (Caliendo et al., 2017), or is based on exante simulations (Müller and Steiner, 2013). This paper provides systematic descriptive ex-post evidence on the distributional implications of the German minimum wage on earnings and disposable household incomes. We analyze different measures of hourly-wage and household-income distributions, both, for the group of affected individuals and the entire population. Most approaches identify individuals "affected" by the minimum wage based on pre-reform wages ignoring large job fluctuations and measurement error at the bottom of the wage distribution. In contrast, we define the group of affected by identifying people's relative position in the wage distribution in each respective year. In line with expectations, we find clear evidence for wage increases at the bottom of the wage distribution. Yet, the changes lie below the potential distributional impact that could be achieved under full compliance to the minimum wage. The impact on overall wage inequality is rather small. Moreover, the minimum wage shows itself to be a poor redistributive tool for disposable household income. Confirming ex-ante simulations we do not see affected households benefiting much from the reform. Overall income inequality has even increased slightly as disposable income of poor households grew much less than on average.
Keywords: J31; D31; J00; 330; minimum wage; wage distribution; income distribution